Diabetic foot and lifestyle: Case Report: Pie diabetico y estilo de vida: Reporte de Caso - Rojo García, Danitza Adriana (2021)
Diabetes is still the leading cause of non-traumatic amputation in most Western countries, epidemiological reports indicate that more than a million amputations are performed in people with diabetes each year, this is equivalent to an amputation for diabetes somewhere in the world every 30 seconds, most of these amputations are preceded by ulcers. We present a case of a 39-year-old male patient suffering from diabetes mellitus and uncontrolled hypertension, with late complications, chronic kidney disease, anemia, retinopathy, and ischemic and neuropathic diabetic foot, with indication for amputation. Healthy lifestyles are used, controlling glycemia, hypertension, without requiring medication and reducing proteinuria. There were no adverse effects. With favorable evolution since then. Conclution: A healthy lifestyle is an intervention that the earlier it is used, the greater its benefits, without the risk of adverse effects or unnecessary costs, but even in late stages it has shown benefits in glycemic, hypertensive and renal control.